'Get your own house in order': Qualitative dialogue groups with nonvaccinating parents on how measles outbreaks in their community should be managed - Kerrie Wiley; Penelope Robinson; Chris Degeling; Paul Ward; Julie Leask; Stacy Carter (Wiley, 2022)
Abstract Objective Communities with high levels of vaccine rejection present unique challenges to vaccine‐preventable disease outbreak management. We sought perspectives of nonvaccinating parents to inform public health responses in such communities. Methods Nineteen purposively sampled nonvaccinating Australian parents participated in one of seven online dialogue groups. We asked what they thought parents, school principals and public health professionals should do in a hypothetical school measles outbreak and used a framework approach to data analysis. Results Parents' views were grounded in strong beliefs in parental responsibility and the belief that vaccines are not effective, thus unvaccinated children do not therefore pose a threat. They then reasoned that the forced exclusion of unvaccinated children from school in a measles outbreak was disproportionate to the risk they pose, and their child's right to education should not be overridden. Nonvaccinating parents judged that all parents should keep sick children at home regardless of disease or vaccination status; that school principals should communicate directly with parents and avoid using social media; that public health professionals should provide information to parents so they can decide for themselves about excluding their children from school; that public health responses should avoid accidental identification of unvaccinated children and that mainstream media should be avoided as a communication tool. Conclusion Nonvaccinating parents do not always agree with current Australian approaches to measles outbreak management. Their perspectives can inform approaches to outbreak responses in communities with high levels of vaccine rejection. Patient or Public Contribution We sought input from individuals who did and did not vaccinate on study design in its early phases. Individual conversations were used deliberately as we felt the group advisory situation may have felt less safe for nonvaccinating parents, given the divisive and often hostile nature of the topic.